Does Tibialis Posterior Dysfunction Correlate with Overall Foot Deformity in Progressive Collapsing Foot Deformity?. Issue 2 (April 2022) - Lalevée, Matthieu; Mansur, Nacime S.; Carvalho, Kepler; Walt, Jennifer S.; Vivtcharenko, Victoria; Tazegul, Tutku; Lintz, Francois; Dibbern, Kevin N.; de Cesar Netto, Cesar
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: Posterior Tibial Tendon (PTT) dysfunction is considered to play an important role in Adult Acquired Flatfoot Deformity recently renamed Progressive Collapsing Foot Deformity (PCFD). Previous flatfoot classifications are mainly based on a progressive mechanical failure of the PTT causing chronological appearance of deformities. A consensus of experts recently met and decided to remove the central place of the PTT dysfunction from the PCFD classification system. The primary objective of our study was to assess the relation between the PTT clinical status and the three-dimensional overall foot deformity. The secondary objective was to assess the relation between the degeneration of PTT at the MRI and the three- dimensional overall foot deformity. We hypothesized that the more damaged the PTT, the more severe the deformity of the foot. Methods: We retrospectively identified all symptomatic PCFD over 18 years old who consulted our center from 01/01/2019 to 12/31/2020. PCFD with concomitant (< 3 mois) clinical examination, Weight-Bearing CT (WBCT) and MRI were included. PCFD presenting with previous surgical intervention were excluded. Finally 25 PCFD were included in the analysis (19 Women, mean age 53.96+/-14.9 years, mean BMI 33.2+/-8.1 kg/m 2 ;)A PCFD presenting either a deficit on the single heel rise test or a decrease in inversion strength (superior or equal to 3/5) was classified PTT deficient. The MRI of all these PCFD were analyzed, and PTT degeneration was classified according to Deland and Rosenberg classifications. The three-dimensional overall deformity of each PCFD was assessed on WBCT by the Foot and Ankle Offset (FAO). Normality of different variables were assessed using Shapiro- Wilk test. Comparisons were performed using Student's t-test or Anova for normal, and Mann-Whitney or Kruskal-Wallis's test for non-normal variables. Results: Patients with clinically deficient PTT (13/25 PCFD, 52%) had a mean FAO of 7.75+/-3.8% whereas patients without PTT deficit (12/25 PCFD, 48%) had a mean FAO of 6.68+/-3.9%, without significant difference between groups (p=0.49). According to Deland classification, 4/25 PTT (16%) were classified grade 0, 7/25 (28%) grade 1, 4/25 (16%) grade 2, 5/25 (20%) grade 3 and 5/25 (20%) grade 4 without any significant difference between groups (p=0.36).According to Rosenberg classification, 4/25 PTT (16%) were classified type 0, 15/25 (60%) type 1, 2/25 (8%) type 2 and 4/25(16%) type 3 without any significant difference between groups (p=0.79).Seven PCFD had a FAO>10%. Among them, 42.9% had a PTT without clinical deficit and 57.1% had a PTT with little or no damage on the MRI. Nine PCFD had a FAO<5%. Among them, 44.4% had a PTT clinically deficient and 22.2% had a PTT with important damage on the MRI. Conclusion: The importance of three-dimensional overall foot deformity in PCFD was neither correlated with the clinical presence or absence of PTT deficiency, nor with the PTT degeneration on MRI in our study. A patient with important deformity may have an intact PTT and a patient with small deformity can present a deficient PTT. Despite the obvious lack of power in this study, it does not appear that PTT plays a significant role in the PCFD overall deformity.